Single nucleotide polymorphisms of genes for EGF, TGF-β and TNF-α in patients with pancreatic carcinoma - Zhang, Lei; Herrle, Florian; Niedergethmann, Marco; Keese, Michael (Cancer genomics & proteomics, 2012)
Aim: To show whether single nucleotide polymorphisms (SNPs) of Epidermal growth factor (EGF)-61*A/G, Transforming growth factor beta 1 (TGF-B1) - 509*T/C and Tumor necrosis factor-alpha (TNF-A) -308*A/G are associated with the survival rate after pancreatic cancer surgery and with the frequency of post-operative complications. Patients and Methods: EGF 61*A/G, TGF-B1-509*T/C and TNF-A-308*A/G genotypes were analyzed in patients who underwent pylorus-preserving pancreaticoduonectomy for pancreatic carcinoma and were determined by means of Polymerase Chain Reaction-Restriction Fragment Length Polymorphism (PCR-RFLP). The association of each genetic polymorphism with clinical and pathological data of the patients and early tumor recurrence were evaluated. Results: A significantly lower median survival duration was found in EGF 61*AA homozygotes, as compared to the AG heterozygous group. There was also a significantly lower median survival duration in the TNF-A-308* AA homozygote group as compared to the AG and GG groups. Survival duration in patients had no correlation with TGF-B1 -509*T/C polymorphism. There was a significantly lower median survival duration in the TNF-A -308* AA homozygous group, as compared to the AG and GG group in a Cox proportional hazard model. The frequency of the TGF-B1 T-allele was higher among patients with leakage of the pancreatic anastomosis. The frequency of the TGF-B1 TC genotype was significantly higher among patients who developed leakage of the biliodigestive anastomosis as compared with the TGF-B1 CC genotype. The frequency of TGF-B1 T-carriers (i.e. TT+TC) was significantly higher among patients with leakage of the biliodigestive anastomosis, as compared to these with the TGF-B1 CC genotype. In a Cox proportional hazard model, only wound infection had a significant correlation with long-term survival duration of patients with pancreatic cancer. Conclusion: There appears to be a significant correlation of the EGF-61* AA and of the TNF-A -308* AA polymorphism with lower survival duration in patients with resectable pancreatic carcinoma. The presence of wound infection was associated with poor prognosis. TGF-B1-509* T-carrying genotypes were more frequent in paitents with severe post-operative complications.